Impact of trauma and surgical treatment on the quality of life of patients with facial fractures - Conforte, J. J. [UNESP]; Alves, C. P. [UNESP]; Sánchez, M.delP.R. [UNESP]; Ponzoni, D. [UNESP] (Elsevier, 2016)
This study assessed the impact of oral and maxillofacial trauma and surgical treatment on the quality of life of patients. The study included 66 patients (age range 18–65 years) with facial fractures; 33 required surgical treatment and 33 required conservative (non-surgical) treatment. Quality of life was evaluated by applying the Oral Health Impact Profile questionnaire (OHIP-14) immediately after diagnosis of the trauma (T1), 30 days after surgery or trauma (T2), and 90 days after surgery or trauma (T3). For the control group (conservative treatment), there was a change in quality of life at T1 and T2. A change in quality of life was found for all of the surgical patients, regardless of the type of fracture and the observation period analyzed. There was no statistical difference when T1, T2, and T3 were compared in cases of zygomatic, Le Fort I, and nasal fractures, however there was an improvement in the quality of life of patients with mandibular fractures (P = 0.0102) and multiple facial fractures (P = 0.0097) at T3. Facial trauma caused the greatest impact on the quality of life of surgical patients at T1. The surgical treatment significantly improved quality of life for patients with mandibular and multiple facial fractures.
Keywords: face; facial bones; facial injuries; maxillary fractures; quality of life